Contestation of Religious Authority in Study Groups: Between Religious Authority and Mass Authority in Aceh - Noviandy, Noviandy; Amin, Muhammad; Zubir, Zubir; Masri, Muhammed Sahrin Bin Haji Masri (Religious: Jurnal Studi Agama-Agama dan Lintas Budaya, 2023)
This article examines the religious authority contestation among study groups in Langsa City, Aceh. The existence of a diversity of study groups does not mean the people there accept the existing plurality. Apart from the growth of religious authority from the Traditional Islamic community, several things also influence it. So the diversity phenomena in religion often become a mass struggle. This research is included in field-library research with qualitative analysis. Data were collected through interviews, documentation, and observation in the study groups. The data were analyzed using a sociology approach and social theory. This article presents two significant findings, including scientific contestation developed by each study group and mass struggle as a confirmation of the authority holder. These two pieces of evidence show that the spread of religious authorities does not necessarily make people accept plurality in religion. Furthermore, Islamic law in Aceh tends to always be in religious contestation.